The Notary's Function in Drafting Fiduciary Security Deeds Involving Patent Rights as Collateral - Yohana Maranatha; Nadia Inggrida Hartono (Universitas Negeri Semarang, 2023)
Government Regulation Number 24 of 2022 on the Creative Economy outlines the implementation of the Intellectual Property-Based Financing Scheme, wherein both banks and non-banking financial institutions leverage Intellectual Property as collateral. This includes fiduciary guarantees over Intellectual Property, contracts within Creative Economy activities, and/or claims within Creative Economy activities. Notably, Patents, a subset of Intellectual Property, can serve as collateral per Article 108 paragraph (1) of Law Number 13 of 2016 concerning Patents, allowing